A fossiliferous spherule-rich bed at the Cretaceous–Paleogene (K–Pg) boundary in Mississippi, USA: Implications for the K–Pg mass extinction event in the Mississippi Embayment and Eastern Gulf Coastal Plain. (November 2018) - Witts, James D.; Landman, Neil H.; Garb, Matthew P.; Boas, Caitlin; Larina, Ekaterina; Rovelli, Remy; Edwards, Lucy E.; Sherrell, Robert M.; Cochran, J. Kirk
Abstract: We describe an outcrop of the Cretaceous–Paleogene (K–Pg) boundary exposed due to construction near New Albany, Union County, Mississippi. It consists of the Owl Creek Formation and overlying Clayton Formation. The Owl Creek Formation is rich in the ammonites Discoscaphites iris and Eubaculites carinatus, which, along with biostratigraphically important dinoflagellate cysts and calcareous nannofossils, indicate deposition occurred within the last 1 million years, most likely last 500 kyrs, of the Cretaceous. The base of the overlying Clayton Formation marks the K–Pg boundary, and consists of a 15–30 cm thick muddy, poorly sorted quartz sand containing abundant spherules representing ejecta derived from the Chicxulub impact event. Impact spherules range in size from 0.5 mm to 1 mm in diameter and are hollow and well preserved, with details such as smaller vesicular spherules enclosed within. The spherules are altered to clay minerals such as smectite and are typical of those found at K–Pg boundary sites in the Gulf of Mexico and beyond. Spherules are scattered throughout the bed, and surface counts suggest an average of 4 spherules per cm 2 . Macrofossils within the spherule bed represent a rich fauna of ammonites, benthic molluscs (bivalves and gastropods), echinoids, as well as crabs and sharks. Macrofossil preservation ranges from whole to fragmentary, with most fossils preserved as internal moulds. The infill of the fossils is lithologically identical to the matrix of the spherule bed, including impact ejecta preserved within phragmocones and body chambers of ammonites, and differs from the underlying Owl Creek Formation. This suggests that the animals were either alive or loosely scattered on the sea floor at the time of deposition. Grain size changes indicate multiple events were responsible for deposition, and together with taphonomic evidence are consistent with dynamic high energy post-impact processes. Later sea level change during the Paleocene is responsible for a sharp contact at the top of the spherule bed. Geochemical evidence from the Owl Creek and Clayton Formations at this locality indicate numerous local paleoenvironmental changes affected the Mississippi Embayment at the time of the K–Pg boundary and mass extinction event. Highlights: Describes new outcrops containing the Cretaceous–Paleogene (K–Pg) boundary from Union County, Mississippi. The fossiliferous Owl Creek Formation contains ammonites and diverse benthic molluscan fauna. Biostratigraphic correlation by macro and microfossils is consistent with deposition during the latest Maastrichtian. A 15–30 cm-thick event bed with macrofossils and impact spherules occurs above the K–Pg boundary. Spherule bed was emplaced rapidly by multiple processes following the Chicxulub impact event.